The Neo-liberal City as Idea and Reality. Issue 2 (2nd April 2016) - Storper, Michael
Abstract: Although there have been substantial changes in the techniques of public management and the rhetoric of urban policy, there is little evidence of the massive withdrawal of the state, de-regulation of city life, reduction in urban public goods, or decline in the role of inter-regional transfers in regional development. These phenomena are frequently cited in the literature arguing that cities and urban policy have become neo-liberal. A principal reason why the critical neo-liberalist literature makes its largely erroneous claim about changes in urban management and policy is that it fails to master liberal economic concepts, and to clearly distinguish them from neo-liberal, illiberal, or laissez-faire reasoning. This paper shows that the literature makes substantial errors in labelling many governmentality practices as neo-liberal, because many of them are caused by pragmatic responses to technological and demographic change, while many others result from the opposite of neo-liberal ideologies, that is, social movements that reject monolithic regulatory state power and press for new, more diversified ways of life. The paper concludes by arguing that the weaknesses of the critical neo-liberalism literature stem from failure to engage with economic and social theory analytics in a disciplined fashion, as well as from normative bias.